Effectiveness of Integrated Al-Islam and Muhammadiyahan Learning Semester Holiday Internship Program (PMLS) at Persyarikatan as Strengthening Understanding of Muhammadiyah Ideology: Efektivitas Pembelajaran Al Islam dan Kemuhammadiyahan Terintegrasi Program Magang Libur Semester (PMLS) di Persyarikatan sebagai Penguatan pemahaman Ideologi Muhammadiyah - Yuanita, Yuanita; Saputra, Adi (Universitas Muhammadiyah Sidoarjo, 2023)
Islamic education in higher education through learning Al Islam and Muhammadiyah (AIKA) plays a very important role as the goal of national education is to produce graduates who have faith and devotion to God Almighty, especially facing future challenges, the need to strengthen Islamic ideology. AIKA education is a conscious and planned effort to believe in and understand the teachings of the Islamic religion in theory. The implementation of the results of strengthening understanding of Muhammadiyah ideology which contains Islamic and Muhammadiyah values is carried out by integrating learning with the semester holiday internship program (PMLS) at the organization. The aim of this research is to describe the effectiveness of AIKA learning which is integrated with PMLS as a means of strengthening understanding of Muhammadiyah ideology. The research subjects were 42 ta`awun students (students who received full scholarships from Muhammadiyah Bangkabelitung University) who were distributed to Muhammadiyah Business Charities (AUM). This research is qualitative descriptive. Data was collected from documentation, interviews and questionnaires in the form of average calculations, then analyzed using the Miles and Huberman Model triangulation. AIK knowledge from the lessons that have been followed and then implementing PMLS can provide meaningful knowledge and experience. Based on the average results of the questionnaire on understanding Muhammadiyah ideology, it was found that 35% Very Understand, 64% Understand, 1% do not understand Muhammadiyah ideology. It can be concluded that AIKA learning which is integrated with PMLS has very good effectiveness when used for learning, especially in understanding AIKA and strengthening Muhammadiyah ideology for ta`awun students at Bangkabelitung Muhammadiyah University.